Efforts To Prepare A Disaster-Ready Campus By Improving Nursing Students' Readiness By Implementing The Tabletop Disaster Exercise Method - Imam Subiyanto; Rismala Kesuma (STIKes RSPAD RSPAD Gatot Soebroto, 2025)
Indonesia is a country with a high risk of disasters; therefore, efforts to improve community preparedness from an early stage are essential, including within higher education institutions. Nursing students, as future healthcare professionals, need adequate knowledge and skills to respond effectively to disaster situations. One educational method that can be used to improve preparedness is the Tabletop Disaster Exercise (TDE). This study aimed to analyze the effect of implementing the TDE method on nursing students' disaster preparedness. This study employed a pre-experimental design using a one-group pretest-posttest approach. The sample consisted of all fourth-semester students of the Diploma III Nursing Program at STIKES RSPAD Gatot Soebroto, totaling 52 respondents selected through total sampling. Data were collected using a disaster preparedness questionnaire administered before and after the TDE intervention. Data were analyzed using a paired statistical test. The results showed an increase in students' preparedness scores after the TDE intervention. Preparedness scores before the intervention ranged from 58 to 75, while post-intervention scores increased to 68–89. Statistical analysis revealed a significant difference between preparedness scores before and after the intervention (p = 0.000; p < 0.05). The study concludes that the Tabletop Disaster Exercise method is effective in improving nursing students' disaster preparedness and can serve as an educational strategy to support the development of a disaster-resilient campus.